Can someone explain to me the derivative of sigmoid function? I am reading NNFS and try to derive sigmoid using the rules that book gives.
Here is my answer:
s(x) = 1/(1+e^-x)
which can be written as
s'(x) = (d/dx)(1 + e^-x)^-1
NNFS says (d/dx)x^y = y * x^(y-1) so
s'(x) = -1 * (1 + e^-x)^-2
but online sources say this is wrong and even the book itself contradicts itself several hundred pages later wtf?
Here is my answer:
s(x) = 1/(1+e^-x)
which can be written as
s'(x) = (d/dx)(1 + e^-x)^-1
NNFS says (d/dx)x^y = y * x^(y-1) so
s'(x) = -1 * (1 + e^-x)^-2
but online sources say this is wrong and even the book itself contradicts itself several hundred pages later wtf?